2000
DOI: 10.1177/0092070300284004
|View full text |Cite
|
Sign up to set email alerts
|

How First Impressions of a Customer Impact Effectiveness in an Initial Sales Encounter

Abstract: First impressions of others affect both the content and outcomes of a variety of interpersonal encounters. In sales encounters, a salesperson’s first impressions of a customer provide a starting point for probing customer needs and for adapting to those needs. This implies that salesperson effectiveness in an initial sales encounter is associated— at least in part—with a salesperson’s first impression of the customer. The reported quasi-experiment is the first study to explore empirically the connection betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 32 publications
0
40
0
2
Order By: Relevance
“…In sales force management literature, selling effectiveness is believed to be a function of the salesperson's knowledge structure, among other variables (e.g., Evans, Kleine, Landry, & Crosby, 2000;Leigh & McGraw, 1989;Rapp, Ahearne, Mathieu, & Schillewaert, 2006;Sharma, Levy, & Evanschitzky, 2000;Sujan, Weitz, & Sujan, 1988;Wilken, Cornelißen, Backhaus, & Schmitz, 2010). Previous research in this area has found that greater knowledge allows salespeople to handle different selling situations more effectively without experiencing undue cognitive stress (Evans et al, 2000). In addition, more effective salespeople were found to have more elaborate scripts (Leong, Busch, & John, 1989), show more variations in selling behaviors across customer types (Leigh & McGraw, 1989), and demonstrate more complete and complex selling strategies (Sharma et al, 2000).…”
Section: Salesperson Knowledgementioning
confidence: 99%
“…In sales force management literature, selling effectiveness is believed to be a function of the salesperson's knowledge structure, among other variables (e.g., Evans, Kleine, Landry, & Crosby, 2000;Leigh & McGraw, 1989;Rapp, Ahearne, Mathieu, & Schillewaert, 2006;Sharma, Levy, & Evanschitzky, 2000;Sujan, Weitz, & Sujan, 1988;Wilken, Cornelißen, Backhaus, & Schmitz, 2010). Previous research in this area has found that greater knowledge allows salespeople to handle different selling situations more effectively without experiencing undue cognitive stress (Evans et al, 2000). In addition, more effective salespeople were found to have more elaborate scripts (Leong, Busch, & John, 1989), show more variations in selling behaviors across customer types (Leigh & McGraw, 1989), and demonstrate more complete and complex selling strategies (Sharma et al, 2000).…”
Section: Salesperson Knowledgementioning
confidence: 99%
“…Branding is prerequisite of relationship and strong branding helps a customer differentiate a brand from the other products. Brand equity tells us how a person thinks about the quality of the product (Aaker, 1996;Dwyer, 1997;Evans et al, 2000;Kim et al, 2001;Kumar & Petersen, 2005).…”
Section: Brand Equitymentioning
confidence: 99%
“…Transactional or sales formula approach (Berger & Nasr, 1998;Rust et al, 2001) and attitudinal customer equity approach (Anderson & Simester, 2004;Evans et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Extant research on service quality in retail specifies salespeople as important contributors to optimal service delivery through which a retailer could be distinguished as superior and could gain a competitive edge (Clopton et al, 2001;Evans et al, 2000;Goff et al, 1997;Grewal & Sharma, 1991;Jacobs et al, 2000;Reynolds & Beatty, 1999;Sharma & Levy, 1995). Not surprising then, is the fact that many retailers nowadays often refer to their salespeople as either a sales assistants or sales executives to acknowledge their potential contribution in the work place.…”
Section: Introduction and Motivation For The Studymentioning
confidence: 99%
“…Despite an abundance of research on the salesperson per se, the role of a salesperson apparently still seems ill structured (Evans et al, 2000). Attempts to understand and improve salespeople's performance in retail have generated a considerable amount of research (Churchill et al, 1990:334, 335;Plank & Reid, 1994).…”
Section: Introduction and Motivation For The Studymentioning
confidence: 99%